Properties of Natural Fiber Cement Materials Containing Coconut Coir and Oil Palm Fibers for Manufacture of Building Materials - Lertwattanaruk, Pusit; Suntijitto, Anchisa (Journal of Architectural/Planning Research and Studies (JARS), 2018)
This article presents an investigation of the properties of cellulose fiber cement products, applicable for a hot-humid climate such as Thailand’s. These materials were made of cement paste containing coconut coir fibers and oil palm residues, both waste products from agricultural manufacturing in Thailand. They are intended to be used as roof sheet and siding materials to reduce heat transfer through buildings and energy conservation. The investigation focused mainly on the effects of both cellulose fibers on the physical, mechanical and thermal properties of products, as determined in accordance with the ASTM and JIS standards. From the results, the mixtures of fiber cement products containing 5% of both cellulose fibers by weight of Portland cement yielded optimal physical and mechanical properties. Furthermore, the thermal conductivity of the fiber cement pastes was 66% less than that of the control specimens, resulting in reduced energy consumption for air conditioning in residential buildings.